The new basel capital accord - Gup, Benton E. (New York : Thomson, 2004)
This book places emphasis on bank's internal controls, increased flexibility in risk management, and more risk sensitivity. It explicitly recognizes credit risk, market risk, and operational risk.
Includes bibliographical references and index.
osa 23/07/14
Loans
Keywords: Bank capital; Bank management; Credit; Risk management